Kinetic evidence for interaction of TMPyP4 with two different G-quadruplex conformations of human telomeric DNA - Pérez-Arnaiz, Cristina; Busto, Natalia; Santolaya, Javier; Leal, José M.; Barone, Giampaolo; García, Begoña (Biochimica et biophysica acta, 2018)
Stabilization of G-quadruplex helices by small ligands has attracted growing attention because they inhibit the activity of the enzyme telomerase, which is overexpressed in >80% cancer cells. TMPyP4, one of the most studied G-quadruplex ligands, is used as a model to show that the ligands can exhibit different binding features with different conformations of a human telomeric specific sequence. UV–Vis, FRET melting Assay, Isothermal Titration Calorimetry, Time-resolved Fluorescence lifetime, T-Jump and Molecular Dynamics. TMPyP4 yields two different complexes with two Tel22 telomeric conformations in the presence of Na+ or K+. T-Jump kinetic experiments show that the rates of formation and dissociation of these complexes in the ms time scale differ by one order of magnitude. MD simulations reveal that, in K+ buffer, “hybrid 1” conformation yields kinetic constants on interaction with TMPyP4 one order lower than “hybrid 2”. The binding involves π–π stacking with external loop bases. For the first time we show that for a particular buffer TMPyP4 interacts in a kinetically different way with the two Tel22 conformations even if the complexes formed are thermodynamically indistinguishable. G-quadruplexes, endowed with technological applications and potential impact on regulation mechanisms, define a new research field. The possibility of building different conformations from same sequence is a complex issue that confers G-quadruplexes very interesting features. The obtaining of reliable kinetic data constitutes an efficient tool to determine reaction mechanisms between conformations and small molecules. •Reactions of TMPyP4 with hybrid-1 and hybrid-2 Tel22 telomeric conformations are observed.•The formation and dissociation reaction rates require T-jump to be monitored.•The fastest reaction in K+ buffer involves hybrid-1.•TMPyP4 binds to the G-quadruplex groove with hybrid-1 and hybrid-2.•Tel22/TMPyP4 complexes are thermodynamically indiscernible in a particular buffer.